Parameters influencing the maximum controllable current in gate commutated thyristors - Lophitis, Neophytos; Antoniou, Marina; Udrea, Florin; Nistor, Iulian; Arnold, Martin; Wikstrom, Tobias; Vobecky, Jan (My University, 2014)
The model of interconnected numerical device segments can give a prediction on the dynamic performance of large area full wafer devices such as the Gate Commutated Thyristors (GCTs) and can be used as an optimisation tool for designing GCTs. In this study the authors evaluate the relative importance of the shallow p-base thickness, its peak concentration, the depth of the p-base and the buffer peak concentration. © The Institution of Engineering and Technology 2014.
Keywords: Digital communication systems; Software engineering